Using Thermal Springs to Quantify Deep Groundwater Flow and Its Thermal Footprint in the Alps and a Comparison With North American Orogens. Issue 22 (21st November 2020) - Luijendijk, Elco; Winter, Theis; Köhler, Saskia; Ferguson, Grant; von Hagke, Christoph; Scibek, Jacek
Abstract: The extent of deep groundwater flow in mountain belts and its thermal effects are uncertain. Here, we use a new database of discharge, temperature, and composition of thermal springs in the Alps to estimate the extent of deep groundwater flow and its contribution to the groundwater and heat budget. The results indicate that thermal springs are fed exclusively by meteoric water and make up 0.1% of the total groundwater budget. Spring water circulates on average to a depth of at least 2 km. The net heat extracted from the subsurface equals 1% of the background heat flow, which equals an average thermal footprint of 7 km 2 . Cooling by downward flow and heating by upward flow are three and two times higher than the net heat flow, respectively. Comparison with North American orogens shows that hydrothermal activity is higher in areas with high relief or areas under extension. Plain Language Summary: Groundwater that originates as rainfall may reach considerable depths in mountain belts. Groundwater can also transport heat and affect subsurface temperatures in mountain belts. However, the amount of groundwater that circulates to deeper levels and the extent to which it affects subsurface temperatures is largely unknown. Here we analyze newly compiled data from hot springs in the Alps to quantify groundwater flow and its thermal effects. On average the groundwater discharging in springs reaches a depth of at least 2 km. The thermal spring water makes up a very small portion (0.1%) of all the groundwater in the Alps, while almost all of the groundwater flows out into rivers and lakes or is evapotranspired. However, the groundwater that feeds springs does affect temperatures of rocks considerably. In areas where the water infiltrates and flows downward, it cools the subsurface, whereas near springs the water flows upward and heats the subsurface. Key Points: Thermal springs in the Alps are exclusively fed by meteoric water, which on average circulates to a depth of at least 2 km On average the contributing area of springs in the Alps is 0.6 km 2 and the thermal footprint is 7 km 2 Comparison with North American orogens indicates that hydrothermal activity is highest in orogens with high relief or undergoing extension